ANALISIS WACANA KRITIS THEO VAN LEEUWEN TERHADAP PEMBERITAAN ANIES DI TOLAK ISI SEMINAR DI UGM - Fahmi Ismail Marzuqi; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
This research aims to examine the strategies of inclusion and exclusion used by Republika.com in relation to the news coverage titled